2018
DOI: 10.1155/2018/5796102
|View full text |Cite
|
Sign up to set email alerts
|

Gossypol from Cottonseeds Ameliorates Glucose Uptake by Mimicking Insulin Signaling and Improves Glucose Homeostasis in Mice with Streptozotocin‐Induced Diabetes

Abstract: Glucose absorption from the gut and glucose uptake into muscles are vital for the regulation of glucose homeostasis. In the current study, we determined if gossypol (GSP) reduces postprandial hyperglycemia or enhances glucose uptake; we also investigated the molecular mechanisms underlying those processes in vitro and in vivo. GSP strongly and concentration dependently inhibited α-glucosidase by functioning as a competitive inhibitor with IC50 value of 0.67 ± 0.44. GSP activated the insulin receptor substrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 39 publications
(42 reference statements)
1
17
0
Order By: Relevance
“…The ability of polyphenol compounds derived from soybeans to inhibit α-glucosidase ( Figure 1B-E) was measured to identify which compound is most effective. Acarbose ( Figure 1A) is an anti-diabetic drug [19] and was used as a positive control in the α-glucosidase inhibition assays [29]. All compounds tested reduce α-glucosidase activity in a concentration-dependent manner ( Figure 1F, grey columns).…”
Section: Potential Of Phytoalexins Derived From Soybeans To Inhibit αmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of polyphenol compounds derived from soybeans to inhibit α-glucosidase ( Figure 1B-E) was measured to identify which compound is most effective. Acarbose ( Figure 1A) is an anti-diabetic drug [19] and was used as a positive control in the α-glucosidase inhibition assays [29]. All compounds tested reduce α-glucosidase activity in a concentration-dependent manner ( Figure 1F, grey columns).…”
Section: Potential Of Phytoalexins Derived From Soybeans To Inhibit αmentioning
confidence: 99%
“…In individuals with type 2 diabetes, α-glucosidase induces postprandial hyperglycemia by breaking di-, tri-, and oligosaccharides into monosaccharides, and α-glucosidase inhibitors delay carbohydrate digestion and absorption, thereby attenuating postprandial hyperglycemia [17]. The anti-diabetic potential of α-glucosidase inhibition has been seen with p-nitrophenyl α-D-glucopyranoside (pNPG), and there is mounting evidence that various α-glucosidase inhibitors produced by plants such as legumes also exert anti-diabetic effects [18][19][20].In the present study, we first compared the ability of four polyphenol compounds (glyceollin, genistein, luteolin, and daidzein) derived from soybeans to inhibit α-glucosidase, and then studied the inhibitory mechanism of action by calculating the K i values of the four polyphenol compounds. We also investigated the synergistic effects between glyceollin and the other three polyphenol compounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several plants rich in terpenes, such as sesquiterpenes found in C. xanthocarpa have been shown an effect on blood glucose levels (Alam et al, 2018;Belhadj et al, 2018). Considering the presence of terpenoids in the extract, among them the caryophyllene that previously demonstrated anti-diabetic activity (Basha and Sankaranarayanan, 2014), the observed effect on glycemia may be due to the presence of these compounds.…”
Section: Effect Of Campomanesia Xanthocarpa Seeds Extract On Oral Glumentioning
confidence: 96%
“…Some plants with properties similar to antidiabetic α-glucosidase inhibitor drugs, such as acarbose, were identified (Kumar et al, 2011;Henriques, 2017). Additionally, studies have shown that sesquiterpenes, present in large quantities in the extract of C. xanthocarpa, have the ability to inhibit α-glycosidases improving glucose metabolism (Alam et al, 2018) as well as other terpenes (Ding et al, 2018). Figure 4 presents the lipid profile of hyperglycemic rats treated with C. xanthocarpa extract.…”
Section: Inhibitory Effect Of Campomanesia Xanthocarpa Extract On Dismentioning
confidence: 99%